2018
DOI: 10.1007/s00343-019-8200-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal distributions and environmental drivers of diversity and community structure of nosZ-type denitrifiers and anammox bacteria in sediments of the Bohai Sea and North Yellow Sea, China

Abstract: Denitrifi cation and anammox processes are major nitrogen removal processes in coastal ecosystems. However, the spatiotemporal dynamics and driving factors of the diversity and community structure of involved functional bacteria have not been well illustrated in coastal environments, especially in human-dominated ecosystems. In this study, we investigated the distributions of denitrifi ers and anammox bacteria in the eutrophic Bohai Sea and the northern Yellow Sea of China in May and November of 2012 by constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, the influence of salinity on denitrification depends on the long-term salinity adaptation of denitrifying microorganisms (Franklin et al, 2017 ; Wang et al, 2018a ; Murphy et al, 2020 ). Many studies have shown that salinity is the most important factor in structuring communities of denitrifying microorganisms, such as nosZ -denitrifiers (Cai et al, 2019 ; Wang et al, 2019 ; Han et al, 2021 ), and that salinity can affect denitrification rates by altering the abundance and diversity of denitrifying microorganism. In Lake Bosten, there was a significant correlation between the abundance of the nirS and nosZI genes ( r = 0.79, p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the influence of salinity on denitrification depends on the long-term salinity adaptation of denitrifying microorganisms (Franklin et al, 2017 ; Wang et al, 2018a ; Murphy et al, 2020 ). Many studies have shown that salinity is the most important factor in structuring communities of denitrifying microorganisms, such as nosZ -denitrifiers (Cai et al, 2019 ; Wang et al, 2019 ; Han et al, 2021 ), and that salinity can affect denitrification rates by altering the abundance and diversity of denitrifying microorganism. In Lake Bosten, there was a significant correlation between the abundance of the nirS and nosZI genes ( r = 0.79, p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, "Ca. Scalindua" is an organism that has mainly been recovered from marine environments [51,52]. We detected "Ca.…”
Section: Anammox Performance Of Various Genera: Potential Of Marine "...mentioning
confidence: 99%